Case report Closed pyometra in a german Spitz Bitch: clinical case report and surgical discussion (REMUNOM, 2025)
Abstract This study describes a clinical case of closed pyometra in an elderly female German Spitz dog, previously used for breeding. The patient presented with lethargy, abdominal distension, fever, polydipsia and anorexia. The diagnosis was based on physical examination, abdominal ultrasonography and laboratory tests, which indicated leukocytosis, neutrophilia and acute renal dysfunction. The treatment instituted was ovariohysterectomy (OSH), but the animal died in the postoperative period, despite adequate clinical support. The case highlights the need for early diagnosis and preventive spaying in females not intended for breeding, especially in old age.Keywords: Closed pyometra; Preventive castration; Uterine secretion; Geriatric bitches.